A moderated moderation of living arrangements and social support on the relationship between depressive symptoms and medication adherence in patients with heart failure. (29th July 2021) - Lindsay-Rahman, R; Lennie, TA; Moser, DK; Chung, ML
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Nursing Research grant Background: Medication adherence is essential to improve health outcomes in patients with heart failure (HF). Depressive symptoms contribute to decrease adherence behaviors. Although social support is helpful to improving medication adherence, perceived social support (PSS) may differ by living arrangement. How social support and living arrangement contribute to the relationship between depressive symptoms and medication adherence is not well understood in patients with heart failure. Purpose: The purpose of this study was to determine whether perceived social support and living arrangement moderated the association between depressive symptoms and medication adherence. Methods: This was a secondary analysis from outpatients with HF. Depressive symptoms were measured by the Patient Health Questionnaire-9. Perceived social support was assessed using Multidimensional Scale of Perceived Social Support, and patients were grouped into high and low PSS groups using a score of 79, the upper tertile value. Medication adherence was measured objectively by a medication event monitoring system for 3-months. Living arrangement was classified as (1) living with a spouse, (2) living with non-spouse family or friend, or (3) living alone. Moderated moderation analysis was conducted using PROCESS macro (Model 3) in SPSS with 5, 000 bootstrap samples. Results: Of the total of 208 patients (mean age = 61 ± 11.5 years, 64% male), 60% lived with spouse, 22% lived with non-spousal family or friend, and 26% lived alone. Three-way interaction (depressive symptoms*living arrangement*PSS) was significant (p = 0.0324, Figure 1). The effect of depressive symptoms on medication adherence was only significant for two groups (Figure 2): the living alone group with high PSS (effect = - 4.1855, p = 0.0021), and the living with a non-spousal family group with low PSS (effect = -1.0180, p = 0.0349). For these groups, their depressive symptoms were inversely associated with medication adherence. Conclusions: These results suggest that living arrangement and perceived social support are factors to be considered in medication adherence when planning care for patients with depressive symptoms. Future research is needed to explore whether the combined intervention of improving depressive symptoms and social support focusing on instrumental social support effectively increases medication adherence.